Model Integrasi Nilai Islam Dan Sains Beserta Implementasinya Di Dunia Islam - Yiyin Isgandi (Universitas Darussalam Gontor, 2021)
This article aims to classify the integration model of Islamic values and science, and their implementation in the Islamic world. The research method uses library research, which is collecting data from various primary and secondary reference sources relating to the themes discussed. From the discussion, it could be concluded that the integration of islamic values and science is very important and a necessity in modern era. Integration is carried out to face the war of thought of Western secular-liberal, materialistic and atheist hegemony, and fortify themselves from westernized muslim intelectual propaganda, while at the same time improving the attitude of conservative-literal clerics who reject modernity. There are four models of integration; Islamic Scientification, Islamization of Science, habituation of Islamic science based on revelation, and the integration of several integration models. The implementation of Islamic Scientification is strongly dominated by academicians in the teachings of relegion, then strenthening it with scientific evidence. The Islamization of Science is stronlyg dominated by academicians in the field of science, then strengtened with the foundation of the al-Qur'an, hadits, and the thought of muslim scholars. The habituation of islamic science was carried out by scientists who are experts in religious and scientific sciences ontologically, methodologically, and axiologically, and proud of islamic identity. While the combination of two or several models of integration is dominated by educational institutions and academicians that prioritize the goal of proving that Allah created all things, there must be benefits for the universe and awakening people to stay away from dangerous things.